2001
DOI: 10.1007/pl00007950
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the finger skin temperature response to cold provocation

Abstract: The method chosen to interpret the FST response to cold provocation affects the ability of the test to detect an abnormal cold response. The area above the response profile, the percentage of initial temperature at the fifth minute of recovery and the maximum temperature achieved during a 10-min recovery period appear to be the most suitable measures for monitoring vascular function in workers exposed to hand-transmitted vibration. It is suggested that the FST response to cold provocation should be interpreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…The effects of cold water between 15 and 25 0 C on forearm, hand and finger temperatures has been studied by Tikuisis (1991, 1992); Tikuisis and Ducharme (1991); Lindsell and Griffin (2001); Suizu and Harada (2005). An ambient temperature of 21 0 C and a water temperature of 15 0 C resulted in a finger temperature of 15.5 0 C, whereas an ambient temperature of 24 0 C resulted in a finger temperature of 22.1 0 C (Ducharme and Tikuisis, , 1992Tikuisis and Ducharme, 1991;Lindsell and Griffin, 2001;Suizu and Harada, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of cold water between 15 and 25 0 C on forearm, hand and finger temperatures has been studied by Tikuisis (1991, 1992); Tikuisis and Ducharme (1991); Lindsell and Griffin (2001); Suizu and Harada (2005). An ambient temperature of 21 0 C and a water temperature of 15 0 C resulted in a finger temperature of 15.5 0 C, whereas an ambient temperature of 24 0 C resulted in a finger temperature of 22.1 0 C (Ducharme and Tikuisis, , 1992Tikuisis and Ducharme, 1991;Lindsell and Griffin, 2001;Suizu and Harada, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Despite some limitations, it was reported that the repeatability of the test was acceptable for the routine diagnosis 9) and the recovery rate of finger skin temperature after cold-water provocation is one of the useful methods for diagnosing the vascular component of HAVS 10) . There is no consensus on a vascular test that is sufficiently robust to be recommended for the diagnosis of HAVS, and in our study, the temperature change during a 10-min recovery period was used as a criterion for vascular dysfunction, and similar criterion was suggested in other study 11) . Investigation of the validity and reliability of this test method should be followed along with possibility of introducing other measures.…”
Section: Discussionmentioning
confidence: 90%
“…Sensibility and speciWcity of skin thermometry range widely (from 21 to 90% and from 37 to 100%, respectively) as reported by diVerent authors (Lindsell and GriYn 2001); uncontrollable factors like adrenergic activity in tested subjects and diVerences in procedures underlie this wide variability. Lindsell and GriYn (2001) have proposed some thermometric interpretation criteria such as the area-over-curve (AOC), the Wfth minute of recovery/baseline temperature ratio (5REC/BT) and the temperature at the tenth minute of recovery after cold test (10REC); such parameters are the most sensible and speciWc when confronted with Wnger blanching during the test.…”
Section: Introductionmentioning
confidence: 86%